Research on the performance of pump-turbine during the transition process from pump mode to turbine mode - Man, Zhe; Xu, Zhe; Gui, Zhonghua; Han, Wenfu; Zhao, Yifeng; Zhang, Fei; Xu, Lianchen; Zheng, Yuan; Kan, Kan (Frontiers in Energy Research, 2024)
In current engineering, the transition process of pump turbines from pump to turbine mode mainly includes the shutdown process of pump operating and the startup process of turbine operating, and the switching of working conditions mostly depends on the opening and closing of the ball valve. While, this article focuses on the transitional process of pump turbine from pump to turbine condition without relying on ball valve, which will significantly reduce the response time of the unit and enable quick switching of operating conditions in emergency situations. In this study, the torque balance equation is employed to analyze the transition process of the entire flow system from pump to turbine operation. Additionally, the entropy production theory is utilized to investigate the correlation between pressure, flow state, and energy loss in the pump-turbine, shedding light on the changes in external characteristics through the evolution of internal characteristics. Furthermore, the transition process from pump mode to turbine mode is segmented into five stages based on the variations in the guide vanes (GV). The findings reveal that the rotation of GV triggers sharp fluctuations in static pressure, torque, and axial force. During stage four, the initiation of all three GV positions results in an increase in flow rate and torque, accompanied by a decrease in axial force. In stage two, the closure of GV leads to a decrease in pressure within the spiral casing (SC) and stay vanes (SV) domains, coupled with an increase in pressure in the bladeless zone, runner, and draft tube domains. Simultaneously, the pressure difference between both sides of the runner decreases significantly, directly causing a drop in torque and axial force. In stage three, GV closure interrupts the flow in the pump-turbine, resulting in significant backflow in the SC, SV, and runner domains, alongside high-speed circulation in the bladeless area. Moreover, the location of the high entropy production rate (EPR) value within the unit aligns with the reflux zone, indicating considerable energy loss attributable to reflux. The above research results will provide reference for the rapid switching of operating conditions of pump turbines in emergency situations.